(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the incidence of hypocalcaemia in patients undergoing total thyroidectomy. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of General Surgery, Central Park Teaching Hospital, and Lahore from 1st March 2016 to 31st March 2019. Materials and Methods: Two hundred and seventy eight patients who underwent total thyroidectomy for benign multinodular goiter and thyroid carcinoma after ethical committee approval. Euthyroid patients between the ages of 20 to 60 years without any gender bias having ASA class I, II and III were included in the study. Patients having concurrent parathyroid pathologies, redo surgery, coagulation disorders, renal failure and vitamin D deficiency were excluded. Post-operative hypocalcaemia was measure in immediate follow-up period and after 6 months. Results: The mean age of patients was 42.22±9.25 years. The frequency of transient hypocalcaemia was found to be 11.15% and permanent hypocalcaemia was 1.8%. Transient hypocalcaemia varied by statistically significant frequency amongst different age groups (p=0.000) while permanent hypocalcaemia did not vary significantly amongst different age groups (p=0.116). There was no association of development of transient or permanent hypocalcaemia with gender and diagnosis of the patients (p˃0.05). Conclusion: The frequency of transient hypocalcaemia and permanent hypocalcaemia following total thyroidectomy was found to be 11.15% and 1.8% respectively.